PENINGKATAN HASIL BELAJAR PENJUMLAHAN BILANGAN BULAT DENGAN PENDEKATAN PMRI DI KELAS IV SD NEGERI - Ocyusa, Brithia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research aim to to increase learning outcomey of class student of IV SDN 15 Taratak Baru Kecamatan Tanjung Gadang Kabupaten Sijunjung in learning sum of integers. This research was covered because the theacher didn’t give the real problem so the student’s achievement is low. Class action research using Pendekatan Matematika Realistik (PMRI). This Approach PMRI use 4 stages (1) introduction stage, (2) model symbolic development stage, (3) explanation and reason stage (4) closing stage. The result of this research can improve student’s learning outcomes in summing the integers. Kata kunci: Penjumlahan, bilangan bulat, pendekatan PMRI